Analisis Hubungan Kebiasaan Belajar terhadap Prestasi Belajar Matematika Siswa - Nope, Rosiani Feti Thanelab; Suradi, Suradi; Danial, Danial (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze and synthesize the relationship between learning habits and students’ mathematics achievement based on various previous research findings, as well as to identify the factors influencing the strength or weakness of this relationship. The method used is a literature review approach, involving the collection of data from 16 relevant national and international journals via the Google Scholar and Semantic Scholar databases for the publication period 2020–2025. The results indicate that the majority of studies found a positive and significant correlation between learning habits and mathematics achievement, with the contribution of the effect varying between 54% and 71.2%. Effective learning habits, such as time management and note-taking techniques, have been shown to enhance discipline and reduce academic procrastination. However, inconsistencies were also found in the results of some studies, influenced by contextual factors such as students’ prior abilities and the learning strategies employed. The conclusion of this study is that learning habits play a crucial role in improving students’ mathematics achievement, particularly when supported by internal factors such as motivation and self-efficacy, as well as external factors such as parental support. Keywords: Study Habits, Mathematics Learning Achievement, Literature Review.